Cohort Study of Nonmelanoma Skin Cancer and the Risk of Exfoliation Glaucoma. Issue 6 (June 2020) - Kang, Jae H.; VoPham, Trang; Laden, Francine; Rosner, Bernard A.; Wirostko, Barbara; Ritch, Robert; Wiggs, Janey L.; Qureshi, Abrar; Nan, Hongmei; Pasquale, Louis R.
Abstract : Precis: In a cohort study of 120, 307 participants with 25+ years of follow-up, a history of nonmelanoma skin cancer (NMSC) was associated with a 40% higher exfoliation glaucoma (XFG) risk. Purpose: The purpose of this study was to evaluate the relationship between NMSC (a marker of ultraviolet radiation exposure) and XFG. Methods: We performed a cohort study of US women (n=79, 102; 1980-2014) and men (n=41, 205; 1986-2014), aged 40+ years and at risk for glaucoma who reported eye examinations. From 1984 (women)/1988 (men), we asked about basal cell carcinoma or squamous cell carcinoma history separately; in prior years, we asked about any NMSC history in a single question. Squamous cell carcinoma was confirmed with histopathology reports while basal cell carcinoma and any early (<1984/<1988) NMSC history was self-reported. Incident XFG cases (362 women and 83 men) were confirmed with medical records. Using pooled data, we estimated multivariable-adjusted relative risks [MVRRs; 95% confidence intervals (CIs)] with Cox proportional hazards models that were stratified by age (in mo), 2-year time period at risk and average lifetime residential latitude. Results: In multivariable-adjusted analyses, we observed a 40% higher XFG risk with any NMSC history (MVRR=1.40; 95% CI=1.08-1.82); the association was observed even with 4 and 8-year lags in NMSC history. Also, the NMSC association was stronger in younger (below 65 y; MVRR=2.56; 95% CI=1.62-4.05) versus older participants (65 y and above; MVRR=1.25; 95% CI=0.94-1.66; P for interaction=0.01) and those living in the northern latitudes (≥42°N; MVRR=1.92; 95% CI=1.28-2.88) versus more southern latitudes (<42°N; MVRR=1.19; 95% CI=0.86-1.66; P for interaction=0.04). Conclusion: NMSC was associated with higher XFG risk, particularly among younger participants and those living in the Northern US.